Upaya Meningkatkan Hasil Belajar PAI Pada Materi Memahami Pesan Pokok Surat Al-Asr Dengan Menggunakan Metode Index Card Match Di SDN Besuki 4 - Yulailin, Sya'idah; Sufirmansyah, Sufirmansyah; Sunaiyah, Salma (Allimna: Jurnal Pendidikan Profesi Guru, 2022)
This study seeks to improve PAI learning outcomes on the subject of understanding the main message of Surat al-Asr by using the index card match method at SDN Besuki 4. This research is a classroom action research where two cycles are applied to determine changes that occur in the classroom. The implementation of this classroom action research will be carried out by following the action scenario. Along the way, it turns out that there are weaknesses, which will be corrected according to the provisions in the field. Researchers draw conclusions based on the data that has been presented. The conclusions drawn are the basis for implementing the next cycle. In this conclusion will also be obtained answers to the problems found at the beginning of the implementation of the action. Based on the types of difficulties experienced by students, an analysis of thinking is carried out in trying to overcome these difficulties so that student learning outcomes are increasing. The results in this study show First, Cycle I averaged 66 then continued to cycle II an average of 84. So that the average of all meetings was 7.85, thus the average learning outcomes per cycle showed an increasing trend, where in cycle I to cycle II an increase of 2,3. Second, Based on the results of observations showed that there was an increase in student activity in the first cycle, they got good results, so the first cycle was 93.31. In the second cycle of 96.15.